A review on the leaf area index (LAI) in vertical greening systems. (1st February 2023) - De Bock, A.; Belmans, B.; Vanlanduit, S.; Blom, J.; Alvarado-Alvarado, A.A.; Audenaert, A.
Abstract: The leaf area index (LAI) is a key dynamic parameter in Vertical Greening Systems (VGS). It quantifies the total amount of leaf area in the canopy and largely determines the extent of co-benefits of VGS. Whereas many studies on VGS discuss the importance of the LAI, only few elaborate on the parameter itself, how it is determined and what the current limitations are in VGS. Moreover, although there is scientific consensus on the importance of LAI in VGS, specific non-destructive monitoring techniques for continuous LAI monitoring appear to be absent, which results in limited overall data on the LAI of VGS under different spatial and temporal conditions and problems in quantifying the benefits of VGS in practice. To fill these gaps, this paper specifically focuses on the LAI of VGS and its monitoring techniques. An overview of existing LAI monitoring techniques in the field of VGS is presented. To arrive at dedicated techniques, this is complemented by a thorough analysis of LAI monitoring techniques used in other research fields, e.g. agriculture and forestry. It is established that two indirect techniques for LAI monitoring are currently available in the VGS sector, but a proper standardized sampling methodology currently lacks. Monitoring techniques used in other sectors offer opportunities for developing dedicated monitoring methods for VGS, but require further research due to the specific features of VGS systems. Furthermore, guidelines are proposed for a more standardized LAI determination of reporting of LAI values in VGS. Highlights: The importance of LAI in characterizing the benefits of VGS is highlighted. LAI of VGS is poorly established and standardized monitoring techniques are missing. An analysis on the shortcomings in determining and reporting the LAI of VGS is made. A standardized sampling and reporting method is provided. Other sectors in which LAI is better established can provide valuable insights.